Different Ways Of Feeling And Interpreting Physical Phenomena In The Ceramist Practices In Cuéra Village In Bragança (PA) - do Rosario, Samuel Antonio Silva; da Silva, Carlos Aldemir Farias (Seven Editora, 2023)
The present work is part of a doctoral research under development in the Graduate Program in Education in Science and Mathematics at the Federal University of Pará. One of the themes addressed is the teaching of Physics through the process of making clay pots relating traditional knowledge to academic knowledge. The research has as empirical locus the traditional community Vila Cuéra, located on the banks of the Caeté River, in the rural area of the municipality of Bragança, state of Pará, Brazil. Among the objectives of the research, we intend to record the empirical knowledge of ceramic artisans about their production and main techniques. The methodological procedure chosen privileges ethnographic techniques in order to facilitate the understanding of the relationship between Physics and the production of ceramics in the chosen community, especially pots, seeking to establish ties that assist the process of construction of the observed ethnophysical knowledge. DOI: https://doi.org/10.56238/methofocusinterv1-096